Surfactant Protein-D, Fibrinogen, and Interleukin-6 Correlation with Clinical Outcomes in Patients with Chronic Obstructive Pulmonary Disease - Anum Wahid; Hafiz Muhammad Usman; Aiman Wahid; Maria Muddassir; Muddassir Ahmed; Faheem Hadi; Tahir Maqbool (Pakistan Journal of Medical Research, 2025)
Objective: Chronic obstructive pulmonary disease is currently the third leading cause of death worldwide. The current study was designed to see if fibrinogen, interleukin-6 or surfactant protein-D could be used as biomarkers to predict frequency of exacerbations within the frequent exacerbator phenotype.